An Inflammatory Loop Between Spleen-Derived Myeloid Cells and CD4+ T Cells Leads to Accumulation of Long-Lived Plasma Cells That Exacerbates Lupus Autoimmunity - Jang, Eunkyeong; Cho, Somi; Pyo, Sungjin; Nam, Jin-Wu; Youn, Jeehee (Frontiers in Immunology, 2021)
Splenic long-lived plasma cells are abnormally numerous and deleterious in systemic autoimmune diseases, yet how they accumulate remains poorly understood. We demonstrate here that a pathological role of spleen-derived CD11b+Gr-1+ myeloid cells (SPMCs) underpins the accumulation of splenic long-lived plasma cells in a lupus-prone model named sanroque. We found that SPMCs were progressively accumulated in sanroque mice from the early clinical phase. Transcriptome profiles revealed that SPMCs have a predominant shift towards an inflammatory phenotype relative to the bone marrow-derived counterparts and are distinct from neutrophils and monocytes. SPMCs were expanded in situ via splenic extramedullary myelopoiesis under the proinflammatory cytokine milieu during lupus progression. SPMCs promoted the development of IFN-gamma-secreting Th1 and follicular helper T cells, thereby licensing CD4+ T cells to be pathologic activators of SPMCs and plasma cells. SPMCs also directly promoted the survival of plasma cells by providing B-cell activating factor of the TNF family. The frequency of SPMCs correlated with that of splenic long-lived plasma cells. Selective depletion of CD11b+Gr-1+ cells reduced autoantibody production in sanroque mice. Thus, our findings suggest that SPMCs expanded in situ establish a positive feedback loop with CD4+ T cells, leading to accumulation of long-lived plasma cells which exacerbates lupus autoimmunity.